Molecular characterisation of cutaneous melanoma - Nunes, I. (2023)
Introduction: Cutaneous melanoma (CM) is the least frequent but deadliest kind of skin cancer, highlighting the aggressiveness of these tumors. As a result of prolonged exposure to UV radiation, CM harbors one of the highest mutation rates among all malignancies. The three most common mutations occur in BRAF and NRAS genes, both important for the mitogen-activated protein kinase pathway upregulation, and in the telomerase reverse transcriptase promoter, which is linked to a poor prognosis. Although current therapies have improved patients’ overall survival, low response rates and treatment resistance remain major challenges for melanoma treatment. Therefore, melanoma investigations have shifted their interest to microRNAs (miRNAs), like miR-125a, miR- 155, and miR- 579, noncoding RNAs that affect the hallmarks of cancer and are potential melanoma biomarkers. Project Aim: To study the molecular alterations of melanomas, to correlate them with the patients’ clinicopathological data and follow-up, and to identify possible prognostic and/or therapeutic biomarkers. Materials and Methods: The mutational status analysis was performed by the Sanger method in primary tumors, metastatic lymph nodes, and metastases collected at Hospital de Santarém and Hospital dos Capuchos. Whereas miRNA expression, from primary tumors collected at Hospital de Santarém, was analyzed by RT-PCR Results: The median age of the studied series was 65 years, where most.